Paraphenylene diamine (Kala Pathar) poisoning in children of Bahawalpur and surrounding areas (Journal of Fatima Jinnah Medical University, 2022)
Background: Paraphenylene diamine (commonly known as Kala Pathar in Pakistan) poisoning is a common presentation in adults as well as pediatric patients in Southern Punjab. The study was carried out to assess paraphenylene diamine poisoning in pediatric cases.Patients and methods: The cross-sectional study was carried out at Bahawal Victoria Hospital Bahawalpur. All the pediatric cases (
Keywords: Paraphenylene diamine; Poisoning; Pediatric; Suicide